Exploration of the Eleventh Graders Difficulties in Understanding Procedural and Declarative Knowledge in the Laboratory Experiment of Heat Transfer - Tawil, Muhammad; Said, Muhammad Amin; Suryansari, Kemala (Jurnal Pendidikan MIPA, 2023)
The purpose of this study was to describe the factors that caused class XI students to have difficulty mastering procedural knowledge and declarative knowledge in heat experiments at Senior High School 1 Gowa. Pseudo-experiment with a population of 5 (five) class XI with a randomly selected sample of one class XI consisting of 50 students. The tests used procedural knowledge, declarative knowledge and valid and reliable questionnaires. Processing data using descriptive statistics. The findings of this study include that physics teachers do not practice declarative indicators, physics teachers do not practice procedural, the average score of declarative and procedural knowledge is medium and low respectively. The reason students have difficulty mastering procedural knowledge and declarative knowledge is because physics teachers rarely train and teach procedural knowledge and declarative knowledge, and students are rarely given the opportunity to develop their potential in the domains of low-level thinking and high-order thinking.Keywords: declarative knowledge, procedural knowledge, physics learning.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp359-372